Effect of planting spacing towards the growth performance of MRQ 74 using SRI method / Muhammad Nasiruddin Muhammad Nabin - Muhammad Nabin, Muhammad Nasiruddin (Faculty of Plantation and Agrotechnology, 2015)
This experiment was carried out from January until April 2015 at Encik Sulaiman Bin Wagiman's paddy field Kampung Kesang Tasek, Sungai Mati, Johor. This study is to determine the effect of planting spacing toward the growth performance of MRQ 74. The experiment was laid out in a complete randomized design. Three different spacing, Treatment 1 (25cm x 25 cm), Treatment 2 (30cm x 30 ern), Treatment 3 (35cm x 35 cm), was carried out. Treatment 1 (25cm x 25 cm) acted of the control for this experiment. This experiment was conducted using the System of Rice Intensification (SRI) technique. The result showed that Treatment 3 (35cm x 35 cm) got the most significant result in plant growth such as plant height, number of tiller and fresh and dry weight compared to other treatments. Considering spacing (35cm x 35 cm) found to be spacing in this study for better performance of plant growth.